Literatur Review: Pengaruh Kualitas Produk, Harga dan Loyalitas terhadap Kepuasan Konsumen Kopi Nako - Sabrina Luna Rahellea; Muhammad Richo Rianto (Penerbit Goodwood, 2023)
Purpose: This study aims to determine the effect of product quality, price and loyalty on Nako coffee consumer satisfaction. Methodology: This study uses the